The tempo of trait divergence in geographic isolation: Avian speciation across the Marañon Valley of Peru. (1st March 2015) - Winger, Benjamin M.; Bates, John M.
Abstract: Geographic isolation is considered essential to most speciation events, but our understanding of what controls the pace and degree of phenotypic divergence among allopatric populations remains poor. Why do some taxa exhibit phenotypic differentiation across barriers to dispersal, whereas others do not? To test factors controlling phenotypic divergence in allopatry, we employed a comparative phylogeographic approach consisting of replicates of ecologically similar Andean bird species isolated across a major biogeographic barrier, the Marañon Valley of Peru. Our study design leverages variation among codistributed taxa in their degree of plumage, morphometric, and vocal differentiation across the Marañon to examine the tempo of phenotypic evolution. We found that substantial plumage differences between populations required roughly two million years to evolve. In contrast, morphometric trait evolution showed greater idiosyncrasy and stasis. Our results demonstrate that despite a large degree of idiosyncrasy in the relationship between genetic and phenotypic divergence across taxa and environments, comparative studies within regions may reveal predictability in the pace of phenotypic divergence. Our results also suggest that social selection is important for driving differentiation of populations found in similar environments.